2014
DOI: 10.1002/jmv.23912
|View full text |Cite
|
Sign up to set email alerts
|

Distinct differences in clinical manifestation and viral laboratory parameters between children and adults with influenza A(H1N1)pdm09 infection—A retrospective comparative analysis

Abstract: During the influenza pandemic 2009 children and adults differed in the clinical course of the influenza disease. In following the question arose, if the case definitions used within the national and international organizations are an adequate tool for the clinical diagnosis of influenza in children as well as in adults. Therefore medical charts from 146 children and 229 adults were retrospectively analyzed. In addition, the initial viral loads of all 375 patients and the duration of virus shedding of a subset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…As would be expected children have a higher influenza A (H1N1) viral load compared to adults because of less exposure to influenza antigens. However, this finding did not correlate with the occurrence of disease complications (83). …”
Section: Diagnosis Of Viral-induced Ardsmentioning
confidence: 84%
“…As would be expected children have a higher influenza A (H1N1) viral load compared to adults because of less exposure to influenza antigens. However, this finding did not correlate with the occurrence of disease complications (83). …”
Section: Diagnosis Of Viral-induced Ardsmentioning
confidence: 84%
“…In a study of 355 pediatric patients with laboratory‐confirmed influenza‐B, 17.9% developed myositis . During the influenza pandemic in 2009, children developed more frequently myositis as compared to adults . Infections with human T‐cell lymphotropic virus (HTLV‐1) may manifest as axial myositis .…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the causative agents, viral myositis has been reported following infections with influenza‐B , influenza‐A , parainfluenza‐1 , parvoviruses , HTLV‐1 , Epstein‐Barr virus , arboviruses (e.g., dengue myositis) , adenovirus , coxsackie , herpes , human immunodeficiency virus‐1 (HIV‐1) , or chickenpox . Most frequently myositis is due to infection with the influenza or parainfluenza virus .…”
Section: Resultsmentioning
confidence: 99%
“…The moderately high sensitivity observed in this study may relate to the fact that 80% of the ILI and SARI case-patients tested were aged <5 years, and RIDTs have been shown to have relative high sensitivity among young children because of increased influenza viral load compared to older children and adults [26, 27]. The sensitivity of RIDTs can be substantially diminished among adults (~18%), [28] and some studies have shown even lower sensitivity among those ≥65 years (8%) [29–31], leading to underestimation of disease burden [32, 33].…”
Section: Discussionmentioning
confidence: 99%